Digital zenith camera of the University of Latvia. Issue 4 (1st October 2016) - Zariņš, Ansis; Rubans, Augusts; Silabriedis, Gunārs
Abstract: Design of digital zenith camera in Institute of Geodesy and Geoinformatics of the University of Latvia started in 2009. Now, after tests of a prototype, improvements of design and manufacturing of the second version, it has reached operational status. The paper describes construction of camera, features of it's control software. Vertical deflection determination results are discussed.